Heart Failure With Reduced Ejection Fraction Polypill Implementation Strategy in India: A Convergent Parallel Mixed Methods Study - Anubha Agarwal; Raji Devarajan; Salva Balbale; Aashima Chopra; Dorairaj Prabhakaran; Mark D. Huffman; Lisa R. Hirschhorn; Padinhare P. Mohanan (Ubiquity Press, 2024)
Introduction: A polypill-based implementation strategy has been proposed to increase rates of guideline-directed medical therapy (GDMT) in patients with heart failure with reduced ejection fraction. This has the potential to improve mortality and morbidity in India and undertreated populations globally. Methods: We conducted a convergent parallel mixed methods study integrating quantitative data from stakeholder surveys using modified implementation science outcome measures and qualitative data from key informant in-depth interviews. Our objective was to explore physician, nurse, pharmacist, and patient perspectives on a HFrEF polypill implementation strategy in India from January 2021 to April 2021. Quantitative and qualitative data were integrated to develop an Implementation Research Logic Model. Results: Among 69 respondents to the stakeholder survey, there was moderate acceptability (mean [SD] 3.8 [1.0]), appropriateness (3.6 [1.0]), and feasibility (3.7 [1.0]) of HFrEF polypill implementation strategy. Participants in the key-informant in-depth interviews (n = 20) highlighted numerous relative advantages of the HFrEF polypill innovation including potential to simplify medication regimens and improve patient adherence. Key relative disadvantages elucidated, include concerns about side effects and interruption of multiple GDMT medications due to polypill discontinuation for side effects or hospitalizations. Based on this data, the proposed implementation strategies in the Implementation Research Logic Model include 1) HFrEF polypills, 2) HFrEF polypill initiation, titration, and maintenance protocols, and 3) HFrEF polypill laboratory monitoring protocols for safety which we postulate will lead to desired clinical and implementation outcomes through multiple mechanisms including increased medication adherence to a single pill. Conclusion: This study demonstrates that a HFrEF polypill-based implementation strategy is considered acceptable, feasible, and appropriate among healthcare providers in India. We identified contextually relevant determinants, strategies, mechanism, and outcomes outlined in an Implementation Research Logic Model to inform future research to improve heart failure care in South Asia.